Renewable food packaging from PLA-kenaf fibre biocomposite - Anuar, Hazleen; Fuad, Faizah; J., Asma'; Kaiser, Mohammad Rejaul; Ahmad, Zuraida (2010)
Every year more than 100,000,000 polyethylene terephtalate (PET) bottles are used in Malaysia, Singapore and Brunei. Out of this gigantic figure, 85,000,000 PET bottles end up as garbage and caused the landfills to be dumped by the PET bottle toxic wastes that leach into the soil. This may pollute and endangers our environment particularly our drinking water. Hence, the driving force of this project is to minimize the dependence on non-degradable plastic packaging by developing alternative material made of polylactic acid (PLA) and kenaf fibre (KF). PLA-KF biocomposite was extruded and then injection moulded for mechanical characterization. Tensile properties and flexural properties significantly improved at 20 wt% kenaf fibre content. Scanning electron micrograph of tensile fracture specimen has revealed the interaction between fibre and matrix, which supported the increment in mechanical properties. Thermal analysis by means of differential scanning calorimetry (DSC) shows that the amourphous state of PLA was remain unchanged with kenaf fibre content and imply that kenaf fibre does not facilitating nucleation of PLA. From dynamic mechanical analysis (DMA), storage modulus (E’) of the biocomposite is higher as compared to unreinforced PLA, whereas the mechanical loss factor (tan ) decreases with kenaf fibre content which associated to the compatibility of PLA matrix and kenaf fibre. This could suggest that kenaf fibre is a viable source that may be incorporated into PLA to reduce mass of the end product and considerably reduced the cost of raw materials.